2024
DOI: 10.1021/acsomega.3c06745
|View full text |Cite
|
Sign up to set email alerts
|

Cyclodextrin Metal–Organic Frameworks as a Drug Delivery System for Selected Active Pharmaceutical Ingredients

Kristi̅ne Kru̅kle-Be̅rziṇa,
Alons Lends,
Anna Boguszewska-Czubara

Abstract: The cyclodextrin-based metal−organic frameworks (CD MOFs) are a suitable molecular platform for drug delivery systems of various active pharmaceutical ingredients (APIs). The low toxicity and cost-efficient synthesis make CD MOFs an attractive host for the encapsulation of APIs. In this study, we created a model system based on γCD-K MOFs with widely used drugs carmofur (HCFU), 5fluorouracil (5-FU), and salicylic acid (HBA) to study host−guest encapsulation methods using different crystallization protocols. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…This phenomenon suggested that CMCS and EWDP could collaborate to facilitate the entrapment of Cur molecules in MOF-based assemblies, which was in agreement with prior discussions (Figure g,h). Meanwhile, Cur (especially for benzene ring regions) was mainly loaded into the porous microstructure and hydrophobic cavities of MOF via hydrogen bonding and hydrophobic interaction. , Similarly, the typical peaks (1677, 1643, and 1517 cm –1 ) of EWDP also dissipated in CMCS-EWDP-MOF-Cur, indicating the excellent coencapsulation efficiency of nutraceuticals within assemblies. To sum up, the coassembled CMCS-EWDP complex could provide an ideal load of dual nutraceuticals for MOF-based assemblies via tailoring main noncovalent interactions (hydrogen bonding, hydrophobic interaction, and electrostatic interaction).…”
Section: Resultsmentioning
confidence: 93%
“…This phenomenon suggested that CMCS and EWDP could collaborate to facilitate the entrapment of Cur molecules in MOF-based assemblies, which was in agreement with prior discussions (Figure g,h). Meanwhile, Cur (especially for benzene ring regions) was mainly loaded into the porous microstructure and hydrophobic cavities of MOF via hydrogen bonding and hydrophobic interaction. , Similarly, the typical peaks (1677, 1643, and 1517 cm –1 ) of EWDP also dissipated in CMCS-EWDP-MOF-Cur, indicating the excellent coencapsulation efficiency of nutraceuticals within assemblies. To sum up, the coassembled CMCS-EWDP complex could provide an ideal load of dual nutraceuticals for MOF-based assemblies via tailoring main noncovalent interactions (hydrogen bonding, hydrophobic interaction, and electrostatic interaction).…”
Section: Resultsmentioning
confidence: 93%
“…Usually, the ordered structure is crystalline, with high surface area [2]. The structure arrangements create pores and adjustable properties that allows a wide range of applications [3], such as photocatalysis [3][4][5], small molecule storage and separation and separation [6-8], drug delivery [9][10][11], chemical sensing and others [12].…”
Section: Introductionmentioning
confidence: 99%